Kemampuan Model Z- Score dan Model Springate Dalam Memprediksi Financial Distress BPR Multi Artha Sejahtera - Uki Masduki; Adi Rizfal Efriadi; Ermalina Ermalina (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2019)
The purpose of this study was to test the ability of the model or analytical tool used to predict the bankruptcy of the company, namely the Altman's Z-afternoon model and the Springate model of BPR Multi Artha Sejahtera whose license has been revoked by the Financial Services Authority (OJK) through Commissioner Decree Number 16 / KDK.03 / 2016 with company considerations deteriorating. The data used is secondary data, namely the 2012-2015 BPR Multi Artha Sejahtera financial report data obtained from Bank Indonesia reports. The data is then analyzed using the Altman Z-score (Z-Score) and Springate (S-Score) formulas to detect whether or not there are indications of bankruptcy before BPR Multi Artha Sejahtera is actually declared bankrupt. The results of this study concluded that overall, both Z-core and S-Score were able to predict the bankruptcy rate of BPR Multi Artha Sejahtera during 2011 - 2015. In the case of BPR Multi Artha Sejahtera bankruptcy the use of S-Score to predict bankruptcy is more appropriate in predicting bankruptcy.